Exploring Tumor Cell–Platelet Biochemical Interactions by Dielectric Measurements of Blood: A Potential Target for Tumor Detection and Staging - Annamaria Russo; Ester Tellone; Francesco Farsaci (Biology)
This paper aims to investigate the dielectric properties of blood for tumor detection and staging. The application of complex thermodynamic models and the study of the trend over time of some thermodynamic functions have allowed us to highlight the generation of displacement currents caused by changes in charge, i.e., by the activation and consequent accumulation of platelets on migrating tumor cells. Although few studies exist to date in this regard, the technique used has provided promising results, especially in terms of building a database. In this context, the evaluation of the dielectric parameters of healthy and cancerous blood can be exploited for the staging of cancer. The main advantages of this method include easy application, non-invasiveness, low cost, and online monitoring.